Penguatan Pencegahan Hepatitis B melalui Penyuluhan pada Kader dan Ibu Hamil di Kecamatan Mamuju - Abbas Mahmud; Rizki Dyah Haninggar (STIKES Marendeng Majene, 2026)
Chronic Hepatitis B Virus (HBV) infection (Chronic Hepatitis B/CHB) remains a major global health problem. In HBV-endemic regions, vertical transmission or mother-to-child transmission constitutes a serious concern. Hepatitis B virus infection can lead to either acute or chronic hepatitis. A reactive/positive HBsAg test indicates the presence of hepatitis B infection in the body. Hepatitis B affects the liver and is associated with several adverse pregnancy outcomes, including preterm birth, low birth weight (<2500 g), premature rupture of membranes, gestational diabetes, and congenital abnormalities related to HBV infection. It is therefore essential to disseminate information to pregnant women and community health volunteers (kader) regarding the impacts of Hepatitis B infection. The objective of this community service activity is to improve the knowledge of community health volunteers and pregnant women about Hepatitis B infection and the simple urine bilirubin screening test. The proposed solution for addressing the identified problems is to provide assistance and education to health volunteers and pregnant women related to Hepatitis B and the method of urine bilirubin testing. The implementation method involves conducting educational and outreach sessions for the target groups regarding Hepatitis B infection. The target partners of this community service program are community health volunteers (kader) and pregnant women. The method used includes delivering educational materials through health education sessions for volunteers and interactive discussions, preceded by a pre-test and concluded with a post-test. Follow-up activities include mentoring volunteers in providing health counseling on Hepatitis B infection to pregnant women.